Social Media for Islamic Da‘wah and Peaceful Coexistence in Yorubaland, Nigeria - Dauda, Kazeem Oluwaseun (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
This study examined the effect of social media misuse for Islamic Da‘wah on peaceful coexistence in Yorubaland, Nigeria, using a descriptive survey research design and an observational method. Data collected through a validated questionnaire were analyzed using simple percentage statistics. Findings reveal that the emergence of social media has significantly altered the patterns of Islamic Da‘wah globally, but its utilization by certain Yoruba Muslim preachers (Du‘at) has elicited conflicting reactions. It contends that some Yoruba Du‘at has used social media platforms to spread misinformation, hate speech, name-calling, condemnation of fellow Muslims, and character defamation instead of providing forums for discussions on religious tolerance, dialogue, mutual understanding, and peaceful coexistence. This has invariably led to constant hostility and confrontation, disunity among religious sects, mistrust among the Muslim ummah, tensions, and an increasing tide of Islamophobia. Also, non-Muslims are contesting Islamic scholars’ nature of Da‘wah propagation, the viability of their messages, and even the level of religious tolerance in Islam. The study concludes that contemporary Yoruba Du‘at should harness the potential of social media in the course of Da‘wah propagation to promote peaceful coexistence, foster a sense of unity among Muslim ummah, and avoid expressing outbursts that could potentially spark religious violence.